Electrophoretic mobilities of dissolved polyelectrolyte charging agent and suspended non-colloidal titanium during electrophoretic deposition - Lau, Kok-Tee; Sorrell, C.C. (Elsevier, 2011)
Coarse (<= 20 microns) titanium particles were deposited on low-carbon steel substrates by cathodic electrophoretic deposition (EPD) with ethanol as suspension medium and poly(diallyldimethylammonium chloride) (PDADMAC) as polymeric charging agent. Preliminary data on the electrophoretic mobilities and electrical conductivities on the suspensions of these soft particles as well as the solutions themselves as a function of PDADMAC level were used as the basis for the investigation of the EPD parameters in terms of the deposition yield as a function of five experimental parameters: (a) PDADMAC addition level, (b) solids loading, (c) deposition time, (d) applied voltage, and (e) electrode separation. These data were supported by particle sizing by laser diffraction and deposit surface morphology by scanning electron microscopy (SEM). The preceding data demonstrated that Ti particles of 1-20 microns size, electrosterically modified by the PDADMAC charging agent, acted effectively as colloidal particles during EPD. Owing to the non-colloidal nature of the particles and the stabilization of the Ti particles by electrosteric forces, the relevance of the zeta potential is questionable, so the more fundamental parameter of electrophoretic mobility was used. A key finding from the present work is the importance of assessing the electrophoretic mobilities of both the suspensions and solutions since the latter, which normally is overlooked, plays a critical role in the ability to interpret the results meaningfully. Further, algebraic uncoupling of these data plus determination of the deposit yield as a function of charging agent addition allow discrimination between the three main mechanistic stages of the electrokinetics of the process, which are: (1) surface saturation; (2) compression of the diffuse layer, growth of polymer-rich layer, and/or competition between the mobility of Ti and PDADMAC; and (3) little or no decrease in electrophoretic mobility of Ti, establishment of polymer-rich layer, and/or dominance of the mobility of the PDADMAC over that of Ti.